(untitled) (El-Wahat Journal for Research and Studies, 2025)
This Study Aims To Clarify The Role Of Modern Technical Media In Collective Ijtihad, By Dealing With Its Definition, And Importance(Legistation, Nation, Ijtihad It Self, Reality), And Its Forms, Even Direct And Indirect, Official And Free, National And International. After That I Dealt With The Modern Technology And Its Media And Functions (Communicative, Informatics, Imformative), Than I Searched The Positive And Negative Effects Of Using Modern Technical Media In Collective Ijtihad. I Ended With The Horizons Of Collective Ijtihad In The Shadow Of Modern Technology , Related To Ijtihad It Self, And Its Keeping Up With Our Reality And Its Technology And Modern Sciences. Key Words: Ijtihad, Collective Ijtihad, Modern Technology, Technical Media